(untitled) (Innovative professional education, 2024)
The definition of economic competence of future farmers is specified. The content and structure of the economic competence of professional junior bachelors in the organisation and technology of farming as an interdependent combination of motivational and value, cognitive, activity, personal and reflective components are revealed. The main components of the formation of economic competence of future farmers in the process of professional training are characterised.